Role of long non‐coding RNA in drug resistance in non‐small cell lung cancer. Issue 7 (3rd May 2018) - Wang, Leirong; Ma, Leina; Xu, Fei; Zhai, Wenxin; Dong, Shenghua; Yin, Ling; Liu, Jia; Yu, Zhuang
Abstract : Lung cancer is the leading cause of cancer‐associated death, and non‐small cell lung cancer (NSCLC) accounts for 85% of all lung cancer cases. Many drugs have been used to treat NSCLC in order to improve patient prognosis. Platinum‐based chemotherapy is the first‐line treatment for locally advanced or metastatic patients. For patients with activating EGFR mutations, tyrosine kinase inhibitors are the best treatment choice. NSCLC initially exhibits an excellent response to treatment; however, acquired resistance has been observed in many patients, leading to ineffective treatment. Clinical resistance is an impediment in the treatment of patients with advanced NSCLC. Many sequencing technologies have shown that long non‐coding RNA (lncRNA) is expressed differently between drug‐resistant and drug‐sensitive lung cancer cells. We review the literature on lncRNA in drug resistance of NSCLC. The aim of this review is to gain insight into the molecular mechanisms of drug resistance, mainly focusing on the role of lncRNA in NSCLC.